Types of school violence perceived by future educators and the relationship of the dimensions of Emotional Intelligence - Gutiérrez, Nieves (2019)
Introduction: School violence can be manifested itself through different ways or types. Objectives. The aim of this work is to define and identify which are the types of school violence that university students identify the most. As well as analysing the positive or negative relationship that the different dimensions of Emotional Intelligence have over identifying different types of school violence. Method: This is a cross-sectional study that aims to analyse the prevalence of different variables collected in a specific period of time from future educators. The sample consists of 175 Social Education degree students in third and fourth grade. To this effect, two questionnaires have been used: The School Violence Questionnaire Revised (CUVE-R) and the Trait Meta Mood Scale-24 (TMMS-24). Results: The main result of this work highlights the fact that the most identified type of violence corresponds to teacher violence against students. Conclusions: It can be concluded that Emotional Intelligence has a high influence on the perception of this type of violence, with disruption in the classroom being the most identified.